Pengaruh Pemahaman Wajib Pajak, Kualitas Pelayanan Perpajakan, Sanksi Perpajakan, Dan Kondisi Lingkungan Terhadap Tingkat Kepatuhan Wajib Pajak Orang Pribadi(Studi Empiris Pada KPP Pratama Surakarta) - Yuliyanti, Ika; , Dra, Mujiyati, M.Si (2016)
The aim of this study was to determine the level of understanding of the taxpayer, the quality of service tax authorities, tax penalties and taxpayers environment to the level of compliance of individual taxpayers. This study uses a quantitave method using primary data obtained from the questionnaire. The population in this study is an individual taxpayer who is registered in KPP Pratama Surakarta. The number of samples in this study were 100 taxpayers. Sample collection method usimg of convenience sampling technique. The analysis tool includes the validity and reliability test, normality test, multicollinearity, heteroscedasticity test, multiple linier regression, F test, test determination coefficient R, and t test. The results showed that the R² values obtained 0,240 which means that 24% compliance rate individual taxpayers affected by the level of understanding of the taxpayer, the quality of service tax authorities, tax penalties and taxpayers environmentally. The remaining 76% influenced by variables outside the model. T test result showed that the level of understanding of the taxpayer, the quality of service tax authorities, tax penalties and taxpayers environmentally positive effect on the level of compliance of individual taxpayer.